2021
DOI: 10.2174/0929867328666210329123449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Curcumin on Microsomal Enzyme Activities: Drug Interaction and Chemopreventive Studies

Abstract: : Curcumin, a yellow pigment in Asian spice, is a natural polyphenol component of Curcuma longa rhizome. Curcuminoid components include curcumin, demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC). Previous studies established curcumin as a safe agent based on preclinical and clinical evaluations and curcuminoids have been approved by the US Food and Drug Administration (FDA) as “Generally Recognized as Safe” (GRAS). The present review collects and summarizes clinical and preclinical studies of curcumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…In inhibitory experiment with enzyme activity, curcumin inhibited effects on CYP3A4, 1A2, 2E1 and 2C19, with IC 50 of 24.27 μM, 92.60 μM, 172.05 μM and 11.86 μM, and germacrone inhibited effects on the same CYP enzymes, with IC 50 of 3.57 μM, 78.06 μM, 120.35 μM and 17.84 μM, respectively. The results were generally consistent with those reports, which CYP3A4, 1A2 were effected by germacrone [ 24 , 41 ]. This study for curcumin and germacrone on CYP enzyme can enrich their activity and content.…”
Section: Discussionsupporting
confidence: 93%
“…In inhibitory experiment with enzyme activity, curcumin inhibited effects on CYP3A4, 1A2, 2E1 and 2C19, with IC 50 of 24.27 μM, 92.60 μM, 172.05 μM and 11.86 μM, and germacrone inhibited effects on the same CYP enzymes, with IC 50 of 3.57 μM, 78.06 μM, 120.35 μM and 17.84 μM, respectively. The results were generally consistent with those reports, which CYP3A4, 1A2 were effected by germacrone [ 24 , 41 ]. This study for curcumin and germacrone on CYP enzyme can enrich their activity and content.…”
Section: Discussionsupporting
confidence: 93%
“…According to the above results, we speculated that reducing the expression level of enterotoxin protein by down-regulating related genes was one of the reasons why BDMC could inhibit enterotoxin. In addition, it has been reported that enterotoxins could bind to polyphenols [25], and BDMC is a polyphenolic compound with two phenolic hydroxyl groups. The hydrophobicity and hydrogen bonding property of the phenolic hydroxyl group are believed to be easily combined with proteins and this chemical structure could be the second reason of the enterotoxins inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…8-hydroxy-2’-deoxyguanosine (8-OHdG), a potential marker of oxidation-related DNA damage, has been shown to be elevated in patients with NAFLD [ 88 ]. In addition, carboxymethyl lysine (CML) is an AGEs produced as a result of enhanced oxidative stress in NAFLD, and the interaction of AGEs with the receptor for advanced glycosylation end products (RAGE) in hepatocytes can worsen oxidative stress [ 89 , 90 ]. A randomized controlled trial by Mirhafez et al showed that giving phospholipid curcumin capsules (250 mg qd) for 8 weeks significantly reduced 8-OHdG and CML levels in patients with NAFLD, suggesting that curcumin may improve oxidative stress in NAFLD [ 61 ].…”
Section: Clinical Evidence Of Curcumin In Treating Metabolic Diseasesmentioning
confidence: 99%